ANALISIS MANFAAT PENGGUNAAN MOBILE BANKING SEBAGAI ALAT PEMBAYARAN DIGITAL - Rianita, Gustin; Fasa, Muhammad Iqbal (PT. Intelek Cendikiawan Nusantara, 2024)
Mobile banking is a service provided by banks to assist customers in transaction activities via cell phone. There are still many customers who still don't understand how to use this application and how its benefits and effects are in the current era. The aim of this research is to understand the extent of the benefits and influence of technology in transactions, especially using mobile banking, among Indonesian people. As well as seeing the extent to which digital payment tools can influence the way of transactions among the public. The research uses qualitative methods and a descriptive approach. The results of the research show that the benefits of using mobile banking are felt by the public, one of which is carrying out transaction activities.